1989
DOI: 10.1161/01.str.20.7.963
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular lesions on MRI. Facts and theories.

Abstract: P atchy subcortical lesions are frequently identified on magnetic resonance imaging (MRI) of the brain in the elderly. 1 -4 On computed tomography (CT) these lesions appear as periventricular zones of lucency and have been termed "leuko-araiosis" by Hachinski and colleagues. 5Despite limited knowledge of the pathological correlates of the lesions, there has been speculation about their nature, pathophysiology, and clinical significance.Epidemiology Subcortical MRI lesions are most commonly seen in the elderly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
2
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 42 publications
0
28
2
1
Order By: Relevance
“…10 Furthermore, neuropathological studies have documented that chronic vascular injury in the blood vessels of the brain leads to atrophic changes immediately surrounding these damaged vessels. 36,37 These atrophic spaces become filled with extracellular fluid that then appears as WMH on MRI. Thus, it is possible that chronic impairment of the vasodilatory response may contribute, in part, to the development of WMH over time.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, neuropathological studies have documented that chronic vascular injury in the blood vessels of the brain leads to atrophic changes immediately surrounding these damaged vessels. 36,37 These atrophic spaces become filled with extracellular fluid that then appears as WMH on MRI. Thus, it is possible that chronic impairment of the vasodilatory response may contribute, in part, to the development of WMH over time.…”
Section: Discussionmentioning
confidence: 99%
“…DWML are even present in a number of elderly persons without any neurological signs. 37 Fein et al 38 examined patients with extensive DWML on MRI and found no major cognitive or focal neurological deficits. On the other hand, van Swieten et al 39 observed that hypertensive patients with confluent DWML on T2-weighted MRI showed a more pronounced cognitive impairment than hypertensive patients with only "patchy or punctate" hyperin- tensities or than normointense patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown a relation between these lesions and dementia, others have shown no such association. 31 The underlying pathophysiology of this white matter disease is thought to be vascular in origin. In select patients with motor and cognitive deficits, pathological study may show diffuse demyelination of the deep white matter, gliosis, necrosis, small subcortical infarcts, arteriolar sclerosis, and dilation of the ventricular system.…”
Section: Discussionmentioning
confidence: 99%